Nanoencapsulation of bioactive ingredients: trends in pharmaceutical industry and functional foods - MÁRQUEZ FERNÁNDEZ, Diana Margarita (Vitae, 2019)
Multiple researches have allowed the development of nanoencapsulation techniques that ease the controlled or targeted release of bioactive components and favor their incorporation in different foods and medication formulations to improve their bioavailability. Recent studies have facilitated the development of nanoencapsulation systems of different active ingredients for functional foods, comprising phenolic compounds, antioxidants, essential oils, minerals, flavors, fish oils, essential fatty acids, vitamins, antimicrobials, soluble fiber, peptides, lycopene, lutein, β-carotene, phytosterols, iron, calcium, among others, as well as bioactive compounds for therapeutic applications as polyphenols, curcumin, quercetin, resveratrol and epigallocatechin-3-gallate.